The economic consequences of Covid in Spain and how to deal with them - Angel de la Fuente (Applied Economic Analysis, 2021)
Purpose – This paper aims to review the economic impact of Covid in Spain and propose policies to deal with them. Design/methodology/approach – Not relevant. Findings – The pandemic is having a very severe effect, which varies across sectors and regions. Given the severity of the problem, a comprehensive policy strategy is needed. Specific proposals about such a strategy are made, distinguishing between the short and the long run. Originality/value – It provides a discussion about the main measures that have been taken to mitigate the economic consequences of Covid in Spain and about what else should be done.